Mulheres brasileiras na música experimental: uma perspectiva feminista - Neiva, Tânia Mello (2018)
In this work I focus on the theme of women in Brazilian experimental music from a feminist perspective. Since experimental music is a field of production linked to artistic creation and often to the use of technology as well, it is formed from codes of masculinity and is carried out by men. At the same time as a field of questioning of hegemonic practices in music, it reproduces other forms of hegemony and domination within it, such as the social relations of sex, race and class. Women's participation, however, has been growing and having more visibility and space in this field in Brazil, especially since the second decade of the twentyfirst century. The aim of this thesis is to understand the female performance in this field from the trajectory and analysis of works by some artists as well as the analysis of the female representation in some recent initiatives (since 2003) of experimental music, especially in the city of São Paulo. The methodology used was case studies, supported by the bibliographical research on the fields of feminism, gender studies and experimental music, having as main base the tools of oral history. The case studies were about recent promoters and producers of experimental music (focusing on the city of São Paulo) and about six artists who have been performing on the scene. We analyzed five training initiatives in the field in São Paulo, as well as the Sonora Network: music and feminism. We brought back the trajectory and characteristics of these institutions in order to understand the role and participation of women in the quoted field, particularly those of the six artists who are studied in his thesis: Isabel Nogueira, Leandra Lambert, Lilian Campesato, Fernanda Aoki Navarro, Bella and Natasha Maurer. We tried to emphasize the moments of their awareness of the stereotyped place of women in music and of propositional movements of confrontation and resistance to the scenario dominated by men.We adopted as a theoretical framework Marxist materialist feminism that postulates that patriarchy is a system that operates structurally with the capitalist system, and it is not possible to stratify the markings of sex, race and class.The oppression of women, therefore, is also characterized by their races / ethnicities and social class. As a result of the research, we perceived the importance of women's awareness of the scene in relation to the patriarchal oppression they are subjected to, which is materialized in various ways. In the process of raising awareness, women organize and begin to occupy space more formally and affirmatively. Artistically there was the recurrent use of the voice in a nonstereotyped way as well as the re-signification of the use of digital or electronic technology, which moves from oppressor element to element of overcoming. We conclude that the field is opening up to another social conformation, with the possibility of partial transformation from this confrontation.